LIST OF REVIEWERS IN YEAR 2024 - Lib, Waldemar (Journal of Education, Technology and Computer Science, 2024)
LIST OF REVIEWERS IN YEAR 2024 Eunika Baron-Polańczyk – University of Zielona Góra (Poland) Jacek Bartman – University of Rzeszów (Poland) Jarmila Honziková – University of West Bohemia in Pilsen (Czech Republic) Petra Kvasnová – Matej Bel University in Banská Bystrica (Slovakia) Oksana Nagorniuk – National Academy of Agrarian Sciences of Ukraine (Ukraine) Ladislav Rudolf – University of Ostrava (Czech Republic) Elżbieta Sałata – University of Technology and Humanities in Radom (Poland) Hristo Saldzhiev – Trakia University, Stara Zagora (Bulgaria) Ganna Shlikhta – Rivne State University of Humanities (Ukraine) Ján Stebila – Matej Bel University in Banská Bystrica (Slovakia) Viera Tomková – Constantine the Philosopher University in Nitra (Slovakia) Bogusław Twaróg – University of Rzeszów (Poland) Magdalena Urlińska-Berens – Jesuit University Ignatianum in Krakow (Poland) Urszula Ordon – Jan Dlugosz University in Czestochowa (Poland)